Beyond T Staging in the "Treat-All" Era: Severity and Heterogeneity of Kaposi Sarcoma in East Africa. (15th August 2021) - Freeman, Esther E.; Semeere, Aggrey; McMahon, Devon E.; Byakwaga, Helen; Laker-Oketta, Miriam; Regan, Susan; Wenger, Megan; Kasozi, Charles; Ssemakadde, Matthew; Bwana, Mwebesa; Kanyesigye, Michael; Kadama-Makanga, Philippa; et al.
Abstract : Background: Although many patients with Kaposi sarcoma (KS) in sub-Saharan Africa are diagnosed with AIDS Clinical Trials Group (ACTG) T1 disease, T1 staging insufficiently captures clinical heterogeneity of advanced KS. Using a representative community-based sample, we detailed disease severity at diagnosis to inform KS staging and treatment in sub-Saharan Africa. Methods: We performed rapid case ascertainment on people living with HIV, aged 18 years or older, newly diagnosed with KS from 2016 to 2019 at 3 clinic sites in Kenya and Uganda to ascertain disease stage as close as possible to diagnosis. We reported KS severity using ACTG and WHO staging criteria and detailed measurements that are not captured in the current staging systems. Results: We performed rapid case ascertainment within 1 month for 241 adults newly diagnosed with KS out of 389 adult patients with suspected KS. The study was 68% men with median age 35 years and median CD4 count 239. Most of the patients had advanced disease, with 82% qualifying as ACTG T1 and 64% as WHO severe/symptomatic KS. The most common ACTG T1 qualifiers were edema (79%), tumor-associated ulceration (24%), extensive oral KS (9%), pulmonary KS (7%), and gastrointestinal KS (4%). There was marked heterogeneity within T1 KS, with 25% of patients having 2 T1 qualifying symptoms and 3% having 3 or more. Conclusion: Most of the patients newly diagnosed with KS had advanced stage disease, even in the current antiretroviral therapy "treat-all" era. We observed great clinical heterogeneity among advanced stage patients, leading to questions about whether all patients with advanced KS require the same treatment strategy.